INCREASE OF UNIFORMITY AND DISPERSION OF THE STRUCTURE OF ELECTROSLAG INGOT LEDEBURIN STEELS - Davidchenco , Stanislav; Сальников , Анатолій Семенович; Logozinsky , Igor; Bilonik , Igor; Shumykin , Sergey; Gubar , Evgeniy (Scientific Journal "Metallurgy", 2020)
In the article the peculiarities of crystallization of ingots is studied during electroslag remelting. In a watercooled copper crystallizer is provided a directional growth of crystals, high physical homogeneity and solidity of cast metal. However, slag remelting of special steels ledeburite class homogeneity and dispersity of the structure of the bar is insufficient. In the center of the bar is formed rougher carbide mesh, and in close proximity to the wall of the mold homogeneous and particulate structure. As a result of analysis of different ways of improving the quality of ESR bars was found that for the considered steels the most suitable technique of entering into a bath of molten metal inocularea particles or granules, homogeneous in composition to the metal being melted. They contribute to the formation of additional centers of crystallization. On the example of steel KH12MF investigated the possibility of improving the homogeneity and dispersion of the structure of the ingot by introducing during melting of the granules of the inoculants. Work was carried out at JSC "Elektrometal plant "Dneprospetsstal". Electroslag remelting electrodes with a diameter of 175 mm was performed on a furnace OKB 1065 in a crystallizer with a diameter of 300 mm on the flux ANF-6. To enter the granules of inoculants into the liquid bath was used doser "Dose 4". Inoculants consisted isomorphic granules of steel KH12MF spherical value . 0.8-1.2 mm, manufactured by atomization of the melt technology plant of powder metallurgy of the enterprise. Study of the macrostructure was carried out on templeto longitudinal cut along the axis of the bar. Recorded dense, homogeneous macrostructure without defects segregated in nature . On microtemplate of the ingot there are no shrinkage defects in a significantly reduced height shrinkage. Below the shrinkage of the macrostructure of the ingot is also dense and homogeneous. According to the conventional technology, the size of the main trim is at the height of the bar 90 mm (50 kg), which suggests the possibility of reducing it by 20-30 kg (40 to 60 %) .Increase the main technical and economic indicators of melting due to the growth in productivity in ESR and reduced energy consumption.